Σέρρες, μέρες του 1891: Διαφωνίες παραγόντων της Ελληνικής Κοινότητας ως προοίμιο του «κοινοτικού ζητήματος» - Πλαστήρας Κωνσταντίνος Ν. (Μακεδονικά, 2011)
The last decade of the 19th century brought many surprises and problemsconnected with community issues in the town of Serres, especially in thesphere of education.This paper sheds light on various aspects of the question: disputes between the Metropolitan of Serres, Konstantinos Vafidis, the Greek Consul,Aristides Metaxas, and the Principal of the Serres’ High School, Petros Papageorgiou.It presents and comments on hitherto unknown documents, such as a report by Petros Papageorgiou on the organisation of the education, and documents of the Greek Consulate in Serres concerning the strife between community representatives in the town, which portend the «community question», that created so many problems.